THE INFLUENCE OF SOCIAL MEDIA ON LANGUAGE EVOLUTION: A CASE STUDY OF UZBEK AND ENGLISH - Kushkarbekova M. U. (Modern American Journals, 2026)
Language in the digital era evolves at unprecedented speed, shaped by platforms that demand brevity, immediacy, and creativity. This article investigates the impact of social media on linguistic practices among Uzbek and English speakers, with particular attention to slang, emojis, hashtags, and code-switching. Drawing on examples from TikTok, Instagram, and Telegram, the study demonstrates how digital communication fosters hybrid identities and multilingual expression. The findings reveal that while social media enriches linguistic diversity and encourages creativity, it also challenges formal writing standards. The paper argues for pedagogical strategies that promote digital literacy, enabling students to balance informal online registers with academic competence.
Keywords: Social media, language evolution, Uzbek, English, code-switching, emojis, hashtags, digital linguistics